Temperature and strain dependence of the Brillouin frequencies in tapered optical fiber - Jeong, Kyu Hwang; Lee, Kwanil; Song, Kwang Yong; Lee, Sang Bae (FIFTH ASIA-PACIFIC OPTICAL SENSORS CONFERENCE, 2015)
We measured the Brillouin frequency in fiber taper and identified the shift of the Brillouin frequency when strain and temperature changed. As taper diameter decreases, strain coefficient for Brillouin frequency decreases down to 0.0488 MHz/mu epsilon while temperature coefficient is maintained.